Biomolecular NMR Spectroscopy - Evans, Jeremy N S (Oxford University Press, 1995)
Explains the features of biomolecular NMR spectroscopy to advanced undergraduates and postgraduates taking courses in NMR, biological NMR, physical biochemistry, and biophysics. This book introduces the quantum mechanical product operators and the classical vector method. It covers two-, three- and four-dimensional NMR and their applications.